2019
DOI: 10.2147/dmso.s180597
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cystic fibrosis-related diabetes: optimizing care with a multidisciplinary approach</p>

Abstract: Cystic fibrosis-related diabetes (CFRD) is a common complication of cystic fibrosis and can be present in over 50% of adults with the disease. CFRD is associated with poorer clinical outcomes, including accelerated pulmonary function decline and excess morbidity. The management of CFRD is complex and differs from that of type 1 and type 2 diabetes mellitus such that clinicians responsible for the care of people with CFRD must work closely with colleagues across a number of different specialities and discipline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Patients with CFRD have a greater incidence of lung disease and a higher frequency of pulmonary exacerbation than non‐CFRD CF. In addition, diabetes increases mortality in CF 3 . Therefore, early diagnosis and control of blood glucose levels of CF are important.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CFRD have a greater incidence of lung disease and a higher frequency of pulmonary exacerbation than non‐CFRD CF. In addition, diabetes increases mortality in CF 3 . Therefore, early diagnosis and control of blood glucose levels of CF are important.…”
Section: Discussionmentioning
confidence: 99%
“…FEV1 in CF patients with diabetes is markedly reduced in all age groups compared to CF patients without diabetes. Simultaneous liver-pancreas transplantation is associated with an improved BMI in the posttransplant course [56,57].…”
Section: The Treatment Of Portal Hypertension Should Includementioning
confidence: 99%
“…15 Furthermore, it is recommended that people with CFRD should have multi-disciplinary team follow-up (preferably four times per year), be offered diabetes structured education programmes and that HbA1c should be monitored with a target of <7% (<53 mmol/mol). 3,5 Although macrovascular disease is currently rare, 16 microvascular complications are increasingly being recognised as complications of CFRD, particularly with increased duration of diabetes and poorer glycaemic control. 17 Retinopathy, nephropathy and neuropathy are all recognised complications 2,8 and prevalence of retinopathy has been reported from small studies as being equivalent to rates observed in type 1 diabetes.…”
Section: Retinopathy and Microalbuminuria Are Common Microvascular Comentioning
confidence: 99%